Intraprocedural Diffusion-Weighted PROPELLER MRI to Guide Percutaneous Biopsy Needle Placement within Rabbit VX2 Liver Tumors - Deng, Jie (2009)
PURPOSE: To test the hypothesis that diffusion-weighted (DW)-PROPELLER (periodically rotated overlapping parallel lines with enhanced reconstruction) magnetic resonance imaging (MRI) can be used to guide biopsy needle placement during percutaneous interventional procedures to selectively target viable and necrotic tissues within VX2 rabbit liver tumors. MATERIALS AND METHODS: Our institutional Animal Care and Use Committee approved all experiments. In six rabbits implanted with 15 VX2 liver tumors, baseline DWPROPELLER images acquired prior to the interventional procedure were used for apparent diffusion coefficient (ADC) measurements. Next, intraprocedural DW-PROPELLER scans were performed with needle position iteratively adjusted to target viable, necrotic, or intermediate border tissue regions. DW-PROPELLER ADC measurements at the selected needle tip locations were compared with the percentage of tumor necrosis qualitatively assessed at histopathology. RESULTS: DW-PROPELLER images demonstrated intratumoral tissue heterogeneity and clearly depicted the needle tip position within viable and necrotic tumor tissues. Mean ADC measurements within the region-of-interest encompassing the needle tip were highly correlated with histopathologic tumor necrotic tissue assessments. CONCLUSION: DW-PROPELLER is an effective method to selectively position the biopsy needle tip within viable and necrotic tumor tissues. The DW-PROPELLER method may offer an important complementary tool for functional guidance during MR-guided percutaneous procedures.